The Effects of the COVID-19 Pandemic on Postgraduate Endodontic Programs in the United States - Aboubakare, Bianca; Chen, James; Galicia, Johnah C. (Frontiers in Dental Medicine, 2021)
In December 2019, the coronavirus disease 2019 (COVID-19) was first identified as an acute infectious disease in Wuhan, China and subsequently led to an ongoing pandemic. At the onset of the pandemic, dental professionals stood to face the greatest exposure risk to SARS-Cov2 due to aerosolization of fluids from the oral cavity and respiratory airways. As a result, dental professionals, including academic institutions and their students and residents halted much of their operations to minimize exposure risks and potentially slow the spread of infection to peers and patients alike. Currently, there is little in the literature that describes the changes that academic institutions have implemented in the face of pandemics. This article will discuss the chronology, modifications, and possible resultant outcomes of COVID-19 related events in respect to Graduate Endodontic programs in the United States.